Hubungan Kemampuan Kognitif dengan Bahasa Reseptif pada Anak Autisme di Pusat Layanan Disabilitas dan Pendidikan Inklusi Kota Surakarta - Syifaunnafi Lilwalidain; Kiyat Sudrajad (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Background: Autism is a very complex disorder of neurobiological development, which includes disturbances in aspects of behavior, social interaction, communication and language Wulandari et al (2018). Children with good cognitive function tend to speak and speak well. People with good cognitive ability have good language skills and vice versa (Aniswita & Neviyarni, 2020). Purpose: This study aims to determine the relationship between cognitive abilities and verbal communication in autistic children at UPT Center for Disability and Inclusive Education (PLDPI) Surakarta. Methods: This research is a quantitative research with a correlational descriptive research design and cross-sectional data collection. The sampling technique used was purposive sampling with a sample size of 30 autistic children at the Surakarta Disability and Inclusive Education Service Center (PLDPI). The collected data will be analyzed univariately and bivariately. The data analysis technique in this study uses the Spearman rank. Research Results: The results of the data analysis showed that the cognitive abilities of autistic children at PLDPI were below the average (83.3%). Receptive language data for autistic children at PLDPI is below the average (73.3%). The relationship between cognitive abilities and receptive language with a value of p = 0.000 where ρ <0.05 indicates a significant relationship between the two variables. The strength of the correlation shows the value of r = 0.763, which means it has a strong category of correlation strength. Conclusion: There is a positive and strong correlation or relationship between cognitive abilities and receptive language in children with autism at the Surakarta Disability and Inclusive Education Service Center (PLDPI).